Alliances and Power Politics in the Trump Era
XI, 263 p. 3 illus., 2 illus. in color.
Keywords: This volume examines the evolution of US foreign policy since Donald Trump’s accession to the presidency and the strategic challenges confronting the United States in a changing geopolitical environment. Trump has delivered on his promises to break with past policies and this has, for the most part, revealed a policy of retrenchment that has jeopardized US alliances. The book focuses on the current state and future of transatlantic relations, on Washington’s policy in the Middle East and Africa, on the administration’s use of the economic weapon in international relations, but also on the American response to the return of great power competition in the face of an assertive China and resurgent Russia. The contributions gather the inputs of a transatlantic community of scholars combining academics, think-tank fellows, former policy-makers and administration officials from both sides of the Atlantic. Maud Quessard is Associate Professor of US Foreign Policy and Senior Research Fellow at the Institute for Strategic Research at the Paris Military School (IRSEM), France. Frédéric Heurtebize is Associate Professor of US History and Politics at the University of Paris Nanterre, France. Frédérick Gagnon is Professor, holder of the Raoul Dandurand Chair in Strategic and Diplomatic Studies, and Director of the Center for United States Studies at the University of Québec, Canada.